Utilization of natural dyes from Zingiber officinale leaves and Clitoria ternatea flowers to prepare new photosensitisers for dye-sensitised solar cells - Ahmad Ludin, Norasikin; Al-Alwani, Mahmoud A.M.; Mohamad, Abu Bakar; Kadhum, Abd. Amir H.; Hamid, Norul Hisham; Ibrahim, Mohd Adib; Mat Teridi, Mohd Asri; Al-Hakeem, Tarik M. Ali; Mukhlus, Abduljabbar; Sopian, Kamaruzzaman (Electrochemical Science Group, University of Belgrade, 2018)
Chlorophyll and ternatin were extracted from Zingiber officinale leaves and Clitoria ternatea flowers respectively. These natural dyes were applied as sensitisers in TiO2-based dye-sensitised solar cells (DSSCs). Among 10 different solvents, the ethanol extracts revealed the highest absorption spectra of natural dyes extracted from Z. officinale and C. ternatea. A major effect of temperature increase was the increased extraction yield. High chlorophyll and ternatin yields were obtained under extraction temperatures of 80 °C and 70 °C, respectively. A notable decrease in C. ternatea dye concentration at temperatures >70 °C was also observed. High dye concentrations were obtained using acidic extraction solutions, particularly those with a pH value of 4. Experimental results showed that the DSSC fabricated with chlorophyll extracted from Z. officinale leaves exhibited a conversion efficiency of 0.30%, open-circuit voltage (Voc) of 0.56 V, short-circuit current (Isc) of 0.8 mA/cm−2 and fill factor (FF) of 57.93%. The DSSC sensitized with ternatin from C. ternatea flowers displayed a conversion efficiency of 0.13%, Voc of 0.54 V, Isc of 0.3 mA/cm−2 and FF of 81.82%.